The Church of Christ : a treatise on the nature, powers, ordinances, discipline, and government of the Christian Church - Bannerman, James, 1807-1868. (Edinburgh ; Carlisle, Pa. : Banner of Truth Trust, 1974)
Reprint of the 1869 ed. published by T. and T. Clark, Edinburgh. Includes bibliographical references and index.
Keywords: Church; Sacraments; Church polity